Vertical split-ring resonators for plasmon coupling, sensing and metasurface - Wu, Pin Chieh (2018)
Split-ring resonator (SRR), one kind of building block of metamaterials, attracts wide attentions due to the resonance excitation of electric and magnetic dipolar response. The fundamental plasmonic properties and potential applications in novel three dimensional vertical split-ring resonators (VSRRs) are designed and investigated. The resonant properties arose from the electric and magnetic interactions between the VSRR and light are theoretically and experimentally studied. Tuning the configuration of VSRR unit cells is able to generate various novel coupling phenomena in VSRRs, such as plasmon hybridization and Fano resonance. The magnetic resonance plays a key role in plasmon coupling in VSRRs. The VSRR-based refractive-index sensor is demonstrated. Due to the unique structural configuration, the enhanced plasmon fields localized in VSRR gaps can be lifted off from the dielectric substrate, allowing for the increase of sensing volume and enhancing the sensitivity. We perform a VSRR based metasurface for light manipulation in optical communication frequency. By changing the prong heights, the 2π phase modulation can be achieved in VSRR for the design of metasurface which can be used for high areal density integration of metal nanostructures and optoelectronic devices.